Pengembangan, Pelatihan, dan Pendidikan dan Pentingnya Pelatihan Karyawan Perusahaan di Masa Pandemi Covid-19 - Samporno Sejati; Veithzal Rivai Zainal; Lenny Nawangsari (Publikasi Indonesia, 2022)
Human Resources have a very important role for the company. Employees are assets for the company, because the success of the company can be achieved because of the competent employees in the company. With good quality performance from employees, it will have a positive effect on employees and the company itself. Every company that is able to compete must have quality and competent human resources. But to form employees with good performance, of course, the company must provide a training and development program for every employee in the company. The most popular methods of employee development used by companies include training programs and leadership development. And the selection of the type of training technique will be more targeted and effective for achieving company targets. Training as part of education which involves the process of learning to acquire and improve skills outside the applicable education system in a relatively short time with methods that prioritize practice over theory. Meanwhile, skill skills include the understanding of physical skills, social skills, and others. Development of employees tends to have an impact on the future of the career concerned, at the time of training may be seen and will feel the development of individuals in work skills. The selection of the type of training and development method for company employees becomes a crucial fundamental in the process of providing maximum knowledge and skills for an effective and efficient process in achieving output in accordance with the objectives and training design.